An analysis of the impacts of wind power penetration in the power system of southern Brazil. (1st November 2019) - Diuana, Fabio A.; Viviescas, Cindy; Schaeffer, Roberto
Abstract: This paper analyzes the main impacts of high penetration levels of wind power in the power system of Southern Brazil. For this, an hourly operation of the Brazilian Southern power system is simulated using an Economic Dispatch Model. Two main scenarios are explored: a baseline and a wind penetration case, both for 2030 and 2050. To create these scenarios, results from an Integrated Energy Model are used as inputs for the dispatch model. The economic dispatch modeling led to some expected outcomes, such as a reduction in the system generation cost, a reduction in greenhouse-gas emissions, and a greater need for transmission expansion in the wind-power scenarios. Results also show that, even for a power system as flexible as the one in Southern Brazil, wind power penetration impacts can be observed. Moreover, results show that setting thermal power plants to provide secondary reserve can potentially improve the balancing management in hydropower-based systems. Finally, results from linking the Economic Dispatch Model and the Integrated Energy Model showed the need for better combining energy expansion models with power dispatch models that consider both the operation and the transmission system restrictions, in order to have stable and feasible unit commitment schedules. Highlights: Different levels of wind power penetration impact hydropower systems differently. High wind penetration systems require detailed power transmission models. Greater insights can be gained by combining the strengths of various modeling tools. Secondary reserve provided by thermal plants can improve balancing management.